Phsysico-chemical and Sensory Characteristics Evaluation of Bread from Composite Flour (Rice, Cassava, Potato Starch and Soybean) with the Addition of Xanthan Gum - Forianus Waruwu; Elisa Julianti; Sentosa Ginting (Universitas Sumatera Utara, 2015)
This study was conducted to determine the physical, chemical and sensory characteristic of bread from composite flour (rice, cassava, potato starch and soybean) with the addition of xanthan gum. The study used a completely randomized design with two factors : the propotion of rice flour : cassava flour: potato starch : soybean in composite flour (T) ; (30 : 50 : 5 : 5 ; 30 : 50 : 10 : 10 ; 30 : 40 : 25 : 5 ; 30 : 40 : 20 : 10 and 100%) and concentration of xanthan gum (G) ; (0%, 0,5% dan 1%). The parameters analyzed were then analyzed physico-chemically include proximate analysis, color, texture and sensory characteristics. The results showed that interaction of flour proportion in composite flour and xanthan gum concentration had highly significant effect on physicochemical properties (specific volume, browning index, moisture, ash, protein, fat and fiber content),had significant effect on carbohydrate content, but had no significant effect on texture and sensory properties of bread . Propotion of rice flour, cassava, potato starch and soybean 30 : 50 : 10 : 10 in composite flour and 0,5% xanthan gum produced bread with the acceptable quality based on physicochemical properties although they still had the lower sensory properties compared than bread produced from 100% wheat flour. Keywords : bread, composites flour, xanthan gum